Political strategies to overcome climate policy obstructionism - Srivastav, S; Rafaty, R (Cambridge University Press, 2022)
Great socioeconomic transitions bring about the demise of certain industries and the rise of others. The losers of the transition tend to deploy a variety of tactics to obstruct change. We develop a political-economy model of interest group competition and garner evidence of tactics deployed in the global climate movement. From this we deduce a set of strategies for how the climate movement competes against entrenched hydrocarbon interests. Five strategies for overcoming obstructionism emerge: (1) appeasement, which involves compensating the losers; (2) co-optation, which seeks to instigate change by working with incumbents; (3) institutionalism, which involves changes to public institutions to support decarbonization; (4) antagonism, which creates reputational or litigation costs to inaction; and (5) countervailance, which makes low-carbon alternatives more competitive. We argue that each strategy addresses the problem of obstructionism through a different lens, reflecting a diversity of actors and theories of change within the climate movement. The choice of which strategy to pursue depends on the institutional context.